Analisis Penggunaan Politeness Strategi Irai Hyougen (Shuuketsubu) Berdasarkan Jouge Kankei oleh Mahasiswa Bahasa Jepang di Daerah Istimewa Yogyakarta - Rosiah, Rosi; Nikmatulloh, Hamdan (Journal of Japanese Language Education and Linguistics, 2020)
Request Expression or Irai hyougen is an expression widely used in daily life. In its use, Irai hyougen consists of three parts, namely Senkoubu (Prolog), Iraibu (Statement of Request), after the request has a disclose, it will usually continue to make a promise and the expression process ends. Still, the researchers used a reminder to confirm the previous request or the so-called Shuuketsubu. Irai Hyougen Shuuketsubu usually consists of reminiscent expressions and confirmation expressions (Xu, 2007). Irai hyougen is an expression that requires an appropriate communication strategy, so it is essential to know the politeness strategies used in Irai Hyougen Shuuketsubu, especially the reminding expression. The politeness strategy used will not be separated from the jouge kankei relationship. This study aims to find out what expressions used by seniors to juniors, between peers, and juniors to seniors in the college environment and also politeness used. The research data came from Japanese language learners in Yogyakarta Special Region. The method used was quantitative, using semantic formulas to analyze the expression strategies used. The results of this study indicate that senior speakers mostly use the main component in the form of a ban (Kinshi Hyougen), the auxiliary component, and discourse regulator. Colleague speakers used the main component in the form of a prohibition expression (Kinshi Hyougen) and the auxiliary component. In contrast, the junior used the main component and helper component. The politeness used by the three situations was a bald-on record strategy (without strategy) because the speaker and speech partner already know each other well.